1998
DOI: 10.1099/00221287-144-5-1331
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of halobacterial gas vesicles

Abstract: Gas vesicle formation in halophilic archaea is encoded by a DNA region (the vac region) containing 14 different genes: gvpACNO and gvpDEFGHIJKLM. In Halobacterium salinarum PHH1 (which expresses the p-vac region from plasmid pHH1), gas vesicles are spindle shaped, whereas predominantly cylindrical gas vesicles are synthesized by the chromosomal c-vac region of H. salinarum PHH4 and the single chromosomal mc-vac region of Haloferax mediterranei. Homologous complementation of gvp gene clusters derived from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 42 publications
(63 reference statements)
1
55
0
1
Order By: Relevance
“…The inability of pGvpE to activate the c-gvpA promoter has already been recognized during heterologous complementation studies using the p-gvpDEFGHIJKLM unit of the p-vac region to complement the c-gvpACNO genes in Hf. volcanii transformants : no GvpA formation could be observed, suggesting that pGvpE cannot activate the c-gvpA promoter (Offner et al, 1998). This could also be the reason that gas vesicles of Hb.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of pGvpE to activate the c-gvpA promoter has already been recognized during heterologous complementation studies using the p-gvpDEFGHIJKLM unit of the p-vac region to complement the c-gvpACNO genes in Hf. volcanii transformants : no GvpA formation could be observed, suggesting that pGvpE cannot activate the c-gvpA promoter (Offner et al, 1998). This could also be the reason that gas vesicles of Hb.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins assemble into a continuous helical ring that encircles the cylindrical body. 53 It has been suggested that various ratios of these paralogs may modulate local shell architecture, such as cylinder radius and tip shape. 54 The small Hsp20 heat-shock proteins (or alphaHsps) are able to form large oligomeric structures with multiple paralogs.…”
Section: Discussionmentioning
confidence: 99%
“…35 Their structure is that of a cylinder, capped with cones at each end. 53 They are composed primarily of a paralogous family of proteins such as GvpA, GvpJ, and GvpM, some of which occur with additional copies, 54 often encoded within two back-toback, divergently transcribed operons [see Fig. 3(A)].…”
Section: Discussionmentioning
confidence: 99%
“…The wall of the cylinder and caps is 2 nm thick and is formed by ribs of width 4?6 nm, which in halobacterial gas vesicles (Offner et al, 1998) have been shown to represent turns of a shallow spiral. The gas vesicle is rigid (Walsby, 1982) and highly permeable to gases (Walsby, 1969) but impermeable to liquid water, which is excluded by the hydrophobic nature of the inside surface (Worcester, 1975).…”
Section: Introductionmentioning
confidence: 99%